2010
DOI: 10.1080/10420150.2010.494305
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of maleic anhydride onto polyethylene wax by melt ultrasound and solid co-irradiation

Abstract: This paper presents a model study to prepare maleic anhydride (MAH)-grafted polyethylene wax (PEW) by using melt ultrasound followed by solid co-irradiation without any initiator or solvent. The MAH graft degree (G) of the product was determined by titration using a solution of organic alkali tetrabutyl ammonium hydroxide in ethanol, which had good accuracy and reproducibility. The experimental results showed that MAH was successfully grafted onto PEW by this method, and the G was 1.57%. The coirradiation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…FTIR was employed to verify the interaction between the PEW‐g‐MAH and CPO. According to the previous reports, 35 CO vibration peaks at 1860 and 1780 cm −1 in the IR spectrum of PEW‐g‐MAH were weakened after saponification, while two new characteristic absorption peaks appeared at 1571 and 1470 cm −1 (Figure 3d), which were attributed to the COO − stretching vibration after the saponification of PEW‐g‐MAH to form carboxylate. It is found that CO vibration peaks at 1860 and 1780 cm −1 were further weakened, and the relative intensity and width of peaks that appeared at 1571 and 1470 cm −1 became stronger and wider after the incorporation of CPO.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…FTIR was employed to verify the interaction between the PEW‐g‐MAH and CPO. According to the previous reports, 35 CO vibration peaks at 1860 and 1780 cm −1 in the IR spectrum of PEW‐g‐MAH were weakened after saponification, while two new characteristic absorption peaks appeared at 1571 and 1470 cm −1 (Figure 3d), which were attributed to the COO − stretching vibration after the saponification of PEW‐g‐MAH to form carboxylate. It is found that CO vibration peaks at 1860 and 1780 cm −1 were further weakened, and the relative intensity and width of peaks that appeared at 1571 and 1470 cm −1 became stronger and wider after the incorporation of CPO.…”
Section: Resultssupporting
confidence: 65%
“…TEM and FTIR also confirmed the size of our synthesized CPO (<2 nm), which is consistent with previous reports (Figure S1c). [34][35][36] More interestingly, if we replace the oligomer with SiO 2 nanoparticles, the average particle size of the emulsion increases rather than decreases (382 nm), and the stability of the emulsion deteriorates (Table S1).…”
Section: Preparation and Stability Testing Of Cpo-pew-g-mah Emulsionsmentioning
confidence: 99%
“…38,39 Using ultrasound and co-irradiation can increase the GD of PEW-g-MAH to 1.57 %. 40 In this study we obtained MAH-grafted lowmolecular-weight polyethylene with a high GD by melting and studied its structure.…”
Section: Introductionmentioning
confidence: 99%